Accuracy estimation of a stretch-retractable single section continuum manipulator based on inverse kinematics. Issue 5 (19th August 2019) - Wang, Hao; Gao, GuoHua; Xia, Qixiao; Ren, Han; Li, LianShi; Zheng, Yuhang
Abstract : Purpose: The purpose of this paper is to present a novel stretch-retractable single section (SRSS) continuum manipulator which owns three degrees of freedom and higher motion range in three-dimension workspace than regular single continuum manipulator. Moreover, the motion accuracy was analyzed based on the kinematic model. In addition, the experiments were carried out for validation of the theory. Design/methodology/approach: A kinematics model of the SRSS continuum manipulator is presented for analysis on bending, rotating and retracting in its workspace. To discuss the motion accuracy of the SRSS continuum manipulator, the dexterity theory was introduced based on the decomposing of the Jacobian matrix. In addition, the accuracy of motion is estimated based on the inverse kinematics and dexterity theory. To verify the presented theory, the motion of free end was tracked by an electromagnetic positioning system. According to the comparison of experimental value and theoretical analysis, the free end error of SRSS continuum manipulator is less than 6.24 per cent in the region with favorable dexterity. Findings: This paper presents a new stretch-retractable continuum manipulator that the structure was composed of several springs as the backbone. Thus, the SRSS continuum manipulator could own wide motion range depending on its retractable structure. Then, the motion accuracy character of the SRSS continuum manipulator in the different regions of its workspace was obtained both theoretically and experimentally. The results show that the high accuracy region distributes in the vicinity of the outer boundary of the workspace. The motion accuracy gradually decreases with the motion position approaching to the center of its workspace. Research limitations/implications: The presented SRSS continuum manipulator owns three degrees of freedom. The future work would be focused on the two-section structure which will own six degrees of freedom. Practical implications: In this study, the SRSS continuum manipulator could be extended to six degrees of freedom continuum robot with two sections that is less one section than regular six degrees of freedom with three single section continuum manipulator. Originality/value: The value of this study is to propose a SRSS continuum manipulator which owns three degrees of freedom and could stretch and retract to expend workspace, for which the accuracy in different regions of the workspace was analyzed and validated based on the kinematics model and experiments. The results could be feasible to plan the motion space of the SRSS continuum manipulator for keeping in suitable accuracy region.